Establishment of farmed fish welfare biomarkers; A multiomics approach - Magalhães, Cláudia Sofia Ferreira Raposo de (2023)
The sustainability of the aquaculture industry hinges on its ability to operate in harmony with the environment. To achieve this, it is essential to prioritize the welfare of farmed fish minimizing the stress levels associated with aquaculture practices. In this context, it is imperative to conduct a comprehensive study of fish physiological stress. The stress response in fish is initiated by an elaborate endocrine machinery that culminates in an overall metabolic reprogramming induced by the action of glucocorticoids. It can either increase fitness or induce further changes at the whole animal level and impair welfare. This process is orchestrated through a multilayered cellular program, and thus a multiomics approach can provide a holistic overview of the molecular stress response. Knowledge of the key regulators behind the adaptation mechanisms could provide valuable markers of stress to complement the existing measures. Sparus aurata, one of the most important species in Mediterranean aquaculture, was used in this study. Adult fish were subjected to three challenges: overcrowding, net handling, and hypoxia. The plasma proteome was assessed to verify the effect of the different challenges on the fish immune system and to measure the levels of typical stress indicators, i.e., cortisol, glucose, and lactate. A multiomics approach was employed to characterize the hepatic stress response, as the liver is the central organ in mounting the stress response. Lastly, skin mucus was used to identify stress biomarkers as it is easily collectable, and a mucosal tissue known to respond to stress. This work demonstrated that Sparus aurata can adapt better to high stocking densities than to net handling or hypoxia. The latter two challenges induced stress in hepatocytes and promoted several prosurvival pathways, e.g., autophagy, unfolded protein response, and DNA replication stress. Furthermore, a set of 28 candidate biomarkers was identified in the skin mucus, which could be further validated as labbased welfare indicators. This research provides scientific knowledge that can be used to develop species-specific welfare assessment protocols, promote farmed fish safety, and enhance positive societal outcomes while promoting aquaculture sustainability.